Brachial artery trauma as a complication of bicep muscle injury. Issue 1 (2nd January 2023) - Graham, Charles; Bergkvist, Sarah; Kimball, Peter; Taylor, Katelyn; Syed, Mudassir; Mohseni, Michael M.
Abstract: We describe a rare case of injury to a branch of the brachial artery in a 48-year-old man with a bicep musculotendinous injury. His presenting symptoms included severe pain, swelling, and paresthesias in the right upper extremity. Examination revealed significant soft tissue swelling with ecchymoses in the right upper arm with diminished palpable pulses. Imaging revealed a biceps muscle injury along with active arterial extravasation of a branch of the deep brachial artery. Interventional radiology successfully performed coil embolization. Bicep musculotendinous injury is typically characterized by pain, swelling, and decreased strength. Rarely, complications such as compartment syndrome have been reported. Brachial arterial injury has not been implicated in the setting of this entity, especially in the absence of blunt or penetrating trauma, until our current patient's presentation.